Physical activity of women during natural delivery - Wawryków, Agata; Korabiusz, Katarzyna; Fabian - Danielewska, Anna; Niedzielska, Mirela; Janik, Inga; Wawryków, Paweł (Journal of Education, Health and Sport, 2017)
Physical activity is one of the main methods that helps in reducing pain and has a great effect during delivery. It can benefit both mother and child. Physical activity reduces fear and tension during labor and also makes breathing easier. Every woman should be allowed to choose the best and most comfortable body position during labor, usually the vertical position is chosen. It accelerates cervical dilatation, and in the second phase of the childbirth, causes that babies head much easier falls into the birth canal. Moreover, activity during delivery is a very important factor that can improve pain relief. Delivery rooms should be equipped with exercise equipment like: ropes and wallbars, big balls, childbirth stools.